Predictors and consequences of job insecurity: A preliminary study of Malaysian bank employees - Wan Toren Wan Yusoff,; Che Rosmawati Che Mat,; Rosmiza Mohd Zainol, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2014)
Paid work is of fundamental importance in modern societies. For individuals, it serves not only to provide them with a means of financial income but also plays an important role in determining social status and prestige. Based on a quantitative study of 141 bank employees, this paper empirically explores the predictors and consequences of job insecurity components among bank employees in Malaysia. The main purpose of this study is to investigate the role of job security satisfaction in predicting organizational commitment and job performance among bank employees in Malaysia. Furthermore, the study explores the contribution of certain demographic variables such as monthly income, age, marital status, education level, job level, tenure in present job and tenure in present organization, as well as organizational factors such as an organization’s activity and training for explaining variations in the levels of satisfaction with job security among individuals. This study suggests that the relationships between job security satisfaction and both organizational commitment and job performance should provide managers with valuable information for developing plans to inspire and retain organizational commitment and to enhance employees’ performance.